Kecenderungan Objektivitas Pemberitaan Epidemi Virus H5N1 dalam International Herald Tribune Online - Puspita, Birgitta Bestari (Jurnal Ilmu Komunikasi, 2011)
Abstract: Newspapers have to be objective in representing the news to the audience. This research wanted to measure the objectivityâs tendency of the news about H5N1 virus, which attacked Indonesia in year 2003. The newsâ objectivities on International Herald Tribune from January 2005 until December 2006 were being measured with the Westerstahlâs Objectivityâs Principle and content analysis as the method. There are 2 dimensions in Westerstahlâs Objectivityâs Principle. First is factuality, which consists of truth and relevance, and the second one is impartiality which consists of balance and neutral presentation.Â Abstrak: Surat kabar harus obyektif dalam menyajikan berita kepada audiens. Riset ini ingin mengukur kecenderungan obyektivitas berita tentang virus H5N1 yang melanda Indonesia pada tahun 2003. Obyektivitas berita diukur berdasar prinsip-prinsip obyektivitas Westerstahl dan menggunakan metode analisis isi. Ada dua dimensi dalam prinsip-prinsip obyektivitas Westerstahl. Pertama adalah faktualitas yang terdiri dari kebenaran dan relevansi, dan yang kedua adalah imparsialitas yang terdiri dari keseimbangan dan penyajian yang netral.